If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(3n + -4) = (3n + 4) * 8 Reorder the terms: 9(-4 + 3n) = (3n + 4) * 8 (-4 * 9 + 3n * 9) = (3n + 4) * 8 (-36 + 27n) = (3n + 4) * 8 Reorder the terms: -36 + 27n = (4 + 3n) * 8 Reorder the terms for easier multiplication: -36 + 27n = 8(4 + 3n) -36 + 27n = (4 * 8 + 3n * 8) -36 + 27n = (32 + 24n) Solving -36 + 27n = 32 + 24n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-24n' to each side of the equation. -36 + 27n + -24n = 32 + 24n + -24n Combine like terms: 27n + -24n = 3n -36 + 3n = 32 + 24n + -24n Combine like terms: 24n + -24n = 0 -36 + 3n = 32 + 0 -36 + 3n = 32 Add '36' to each side of the equation. -36 + 36 + 3n = 32 + 36 Combine like terms: -36 + 36 = 0 0 + 3n = 32 + 36 3n = 32 + 36 Combine like terms: 32 + 36 = 68 3n = 68 Divide each side by '3'. n = 22.66666667 Simplifying n = 22.66666667
| 8q+12=5q | | -8.3+a=-11.2 | | 3z-4-7-z=-3 | | (2/6x)-(4/3x)+(5/6x^2) | | -105-8x=159+4x | | (2xy-3xy-y)+(2xy-xy)= | | -3x+2=-19 | | 2(x+24)=0 | | P+0.4=-1.7 | | (2v+7)(3v-1)=0 | | p=-17/1 | | r/12=19/10 | | 20.00-1.50y=177 | | 9+-5y= | | -86+n=12 | | 19=2e^4x | | A+6/3=-5 | | 4t-2=6 | | -3y-7-y=13 | | 2x+5+4x+13=120 | | -2x-6=-8 | | -2+7y=11 | | 6x-110=-74 | | 7(3n-1)=(8n+5)+2 | | (Y-3y-5)-(-y-7y+4)= | | 5(-2y+6)=-40 | | 1/3h+4/6=9 | | -16=p-31 | | -176=k-93 | | -4y+5-2y=-13 | | -24-x=0 | | 8x-64+9x-16=90 |